PENERAPAN MODEL SNOWBALL THROWING DALAM UPAYA MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS VII SMP AL WASHLIYAH 8 MEDAN - Gemala Widiyarti (JURNAL TEMATIK, 2014)
Application Snowball Throwing Mode In The Increase Student Achievement In Speaking On The Seventh Class Of Junior High School Al Washliyah 8 Medan. In this research purposed to increase students achievement in speaking by Snowball Throwing mode on the seventh class of junior high school Al Washliyah 8 Medan. This research focused on the increasing speaking aspects linguistics or non linguistics in the learning process. This research do in the SMP Al Washliyah 8 Medan at May until July 2013. The subject of this research is the students of VII SMP Al Washliyah 8 Medan, the amount are 40 student and the object in the research is to increasing the students speaking skills in learning Indonesian Language. This research is classroom action research. This research do by collaborative and participative collaboration with Indonesian language teacher seventh class, she is miss. Wiri Sunarwani S.Pd. To collecting the data using by speaking, observation, interview and digital for getting documentation. This research using analyses descriptive quantitative which support by quantitative data. The real of data getting from trying credibility, transferability, dependability and confirmability. According to the research result, the students achievement in speaking has done by implementation action by Snowball Throwing mode and has increased, that increase can see by indicator of product success. The success of learning can see by passive student and just silent, but after using these mode in the learning, student become more active and have confident when asked for speaking in front of the class. Beside that when the test done shows the speaking achievement and confidents of the student has increase step by step, from the circulation which has done . the result of the score showing has increased at the speaking achievement at the circulation 58,9 increase to the first 77,3 and increase to the second 98,4. So we conclude that, after doing action implementation mode by Snowball Throwing mode get increasing at each circulation. Using this mode learning can helping the student become brave to expressing their idea with fluently. Next, the student can increasing thinking action which critic, logic, systematic and by themselves.